2015
DOI: 10.1371/journal.pone.0141844
|View full text |Cite
|
Sign up to set email alerts
|

A Significant Increase in the Incidence of Central Precocious Puberty among Korean Girls from 2004 to 2010

Abstract: BackgroundFew studies have explored the trends in central precocious puberty (CPP) in Asian populations. This study assessed the prevalence and annual incidence of CPP among Korean children.MethodsUsing data from the Korean Health Insurance Review Agency from 2004 to 2010, we reviewed the records of 21,351 children, including those registered with a diagnosis of CPP for the first time and those diagnosed with CPP who were treated with gonadotropin-releasing hormone analogs.ResultsThe prevalence of CPP was 55.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
92
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 17 publications
7
92
2
2
Order By: Relevance
“…CPP can cause early menarche in girls and result in short adult stature due to early epiphyseal fusion (11). The annual incidence of CPP in girls had significantly increased from 3.3 to 50.4 per 100,000 girls during 2004 to 2010 in Korea (28). The incidence of girls diagnosed with CPP has markedly increased in 21th century and much higher compared to 40 year ago in Denmark (29).…”
Section: Discussionmentioning
confidence: 99%
“…CPP can cause early menarche in girls and result in short adult stature due to early epiphyseal fusion (11). The annual incidence of CPP in girls had significantly increased from 3.3 to 50.4 per 100,000 girls during 2004 to 2010 in Korea (28). The incidence of girls diagnosed with CPP has markedly increased in 21th century and much higher compared to 40 year ago in Denmark (29).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies can help refine the use of FMV urinary gonadotropins as a diagnostic method for pubertal disorders. CPP has become a common reason for visits and referrals to pediatric endocrinologists in Korea [24]. In clinical practice, random basal serum gonadotropins are routinely used as an initial screening method for CPP.…”
Section: Discussionmentioning
confidence: 99%
“…There has been an increase in the incidence and prevalence of precocious puberty as reported in various publications. In a study conducted in Korea, the prevalence of precocious puberty was reported as 55.9 in 100.000 girls [30] . In various studies, 86%-92% of the cases of precocious puberty consisted of female children with a female-to-male ratio ranging from 3:1 to 23:1 [31] .…”
Section: Discussionmentioning
confidence: 99%